Qualitative Research Methods in Sport, Exercise and Health: From Process to Product, 1st edition - Sparkes, Andrew C. (Routledge, 2020)
Qualitative forms of inquiry are a dynamic and exciting area within contemporary research in sport, exercise and health. Students and researchers at all levels are now expected to understand qualitative approaches and be able to employ them in their work. In this comprehensive and in-depth introductory text, Andrew C. Sparkes and Brett Smith take the reader on a journey through the entire qualitative research process that begins with the conceptualization of ideas and the planning of a study, moves through the phases of data collection and analysis, and then explains how findings might be represented in various ways to different audiences. Ethical issues are also explored in detail, as well as the ways that the goodness of qualitative research might be judged by its consumers.